Milking Behaviour of Dairy Buffaloes and Scope for Mechanization/Automation of Milking Operation at Buffalo Farms (Indian Journal of Animal Production and Management, 2024)
Buffaloes have higher milking temperament  scores than crossbred cows and therefore pose  problems for proper milk let-down and efficient milk  removal specially in machine milking. Their alveolar  fraction of milk is relatively higher and cisternal  fraction of milk is lower. The animals with small  cisterns are more susceptible to the short-term  autocrine inhibition of milk secretion in the  mammary gland. For mechanization of milking in  buffaloes they need to be conditioned to machine  milking for appropriate milk ejection in the milking  parlour for a period of about one week. For better  milk ejection in buffaloes and to avoid dry running a  special arrangement to the milking machine  (DualVac arrangement- double vacuum  arrangement) has been suggested as a possible  solution.
Keywords: buffaloes; milking behaviour; automation